2021
DOI: 10.1371/journal.pone.0260384
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial variation in the oral microbiota in multiple sclerosis patients

Abstract: Background Microorganisms in oral cavity are called oral microbiota, while microbiome consists of total genome content of microorganisms in a host. Interaction between host and microorganisms is important in nervous system development and nervous diseases such as Autism, Alzheimer, Parkinson and Multiple Sclerosis (MS). Bacterial infections, as an environmental factor in MS pathogenesis play role in T helper 17(Th17) increase and it enhancing the production of pro-inflammatory cytokines such as Interlukin-21(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Pro-inflammatory factors enhance the inflammatory status of AD patients. 67 PCA results validate that each group's composition of intestinal microbiota changed significantly. The relative distance between the model group and the normal group is wide, the administration group is scattered between the two groups, and WEGN is closest to the normal group.…”
Section: Discussionmentioning
confidence: 53%
“…Pro-inflammatory factors enhance the inflammatory status of AD patients. 67 PCA results validate that each group's composition of intestinal microbiota changed significantly. The relative distance between the model group and the normal group is wide, the administration group is scattered between the two groups, and WEGN is closest to the normal group.…”
Section: Discussionmentioning
confidence: 53%
“…Prevotella spp., a proteolytic/amino acid–degrading bacteria, can break down proteins and peptides into amino acids and degrade them further via specific pathways to produce short-chain fatty acids [ 27 ], and its species are considered commensal microbes in the oral cavity [ 28 ]. However, several recent studies demonstrated that Prevotella is associated with diseases, such as periapical infection [ 29 ], gout [ 30 ], and multiple sclerosis [ 31 ]. Thus, although Prevotella declined in CKD patients which included those with and without hypertension, its role needs further investigation by salivary microbiome transplantation in CKD patients and animal models.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported significant differences in the relative abundance of 23 genera of oral bacteria in migraine patients compared tohealthy subjects, and it was proposed that they contribute to the occurrence of migraine via the nitrate–nitrite–nitric oxide pathway ( 9 ). Oral microorganisms can affect the inflammatory process of multiple sclerosis (MS), and controlling oral infection may slow MS progression ( 10 ). Our results showed that oral microbiota community composition was altered in patients with MG.…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral health, which is associated with an imbalance of oral microbiota community structure and composition, has a major effect on neuroinflammation and has been linked to central nervous system diseases such as Alzheimer's disease (AD), to central nervous system diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), migraine, and multiple sclerosis (MS) (6)(7)(8)(9)(10). However, the relationship between oral microbiota profile and MG has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%